Kinky boots [videorecording (DVD)] - Lauper, Cyndi, 1953- (MVD Visual, 2021)
Factory owner Charlie is struggling to save his family's shoe manufacturing business, and Lola is an entertainer with a wildly exciting idea. This unexpected pair learns to embrace their differences and create a line of sturdy stilettos! But in the end, their biggest achievement is their friendship.